Teacher Learning Management in the Preparation of Lesson Plans at the Muslimat Samalanga Private Middle School, Bireuen Regency - Tgk Armis; Muliani Muliani; Zulfahmi Zulfahmi (Budapest International Research and Critics University, 2022)
What are the supporting and inhibiting factors in teacher learning management in the preparation of lesson plans at the Muslimat Samalanga Private Middle School, Bireuen Regency. This type of descriptive qualitative research. The research technique is in the form of observation, interview and documentation review. The conclusion is the concept of teacher learning management in the preparation of lesson plans at the Muslimat Samalanga Private Middle School, Bireuen Regency through a deliberation mechanism, recruiting competent teachers in the fields being taught. Through deliberation, all tasks contained in the RPP can be carried out properly. The selection of competent and creative teachers will produce educators who are able to implement the concept of learning management in the preparation of lesson plans. Barriers to teacher learning management in preparing lesson plans at the Muslimat Samalanga Private Middle School, Bireuen Regency are the lack of teaching time so that each material in the lesson plans is not achieved and the lack of student capacity because each year the increase in students is always increasing and the lack of time is because the formal education curriculum follows the ministry curriculum national education, the leadership must as much as possible in implementing the curriculum without disturbing the regulations and activities of the pesantren.